Do Prices in the EMU Converge (Non-linearly)? - Ulrich Fritsche; Sarah Lein; Sebastian Weber (Hamburg University, Department Economics and Politics, 2009)
This paper examines the current state of price convergence amongst the eleven initial EMU member states. Special attention is given to possible changes in the convergence process during the euro cash changeover. We apply the sigma-convergence approach using both panel estimates of changes in the deterministic time trend of a coefficient of variation and stochastic kernel-density estimates. We find that convergence took place before 2000, slowed down substantially between 2000 and 2003, and resurfaced after 2003. This points to a non-linear convergence path. We show that stronger convergence is associated with periods of positive and less-dispersed output gaps across member states. There are no big differences between the results for tradables and non-tradables, indicating that Balassa-Samuelson effects are relatively weak.
Keywords: C14; C33; E31; F15; 330; Prices; European Monetary Union; Sigma-convergence; Kernel-density Estimation; Balassa-Samuelson Effect